The promise of human induced pluripotent stem cells in dental research - Srijaya, Thekkeparambil Chandrabose; Pradeep, Padmaja Jayaprasad; Zain, R.B.; Musa, Sabri; Abu Kasim, Noor Hayaty; Govindasamy, Vijayendran (Hindawi, 2012)
Induced pluripotent stem cell-based therapy for treating genetic disorders has become an interesting field of research in recent years. However, there is a paucity of information regarding the applicability of induced pluripotent stem cells in dental research. Recent advances in the use of induced pluripotent stem cells have the potential for developing disease-specific iPSC lines in vitro from patients. Indeed, this has provided a perfect cell source for disease modeling and a better understanding of genetic aberrations, pathogenicity, and drug screening. In this paper, we will summarize the recent progress of the disease-specific iPSC development for various human diseases and try to evaluate the possibility of application of iPS technology in dentistry, including its capacity for reprogramming some genetic orodental diseases. In addition to the easy availability and suitability of dental stem cells, the approach of generating patient-specific pluripotent stem cells will undoubtedly benefit patients suffering from orodental disorders.